Rethinking the Ethics of Corporate Political Activities in a Post-Citizens United Era: Political Equality, Corporate Citizenship, and Market Failures - Néron, Pierre-Yves (Journal of business ethics, 2016)
The aim of this paper is to provide some insights for a normative theory of corporate political activities (CPAs). Such a theory aims to provide theoretical tools to investigate the legitimacy of corporate political involvement and allows us to determine which political activities and relations with government regulators are appropriate or inappropriate, permissible or impermissible, obligatory or forbidden for corporations. After having explored what I call the “normative presumption of legitimacy” of CPAs, this paper identifies three different plausible strategies to criticize and object to corporate political involvement: the “egalitarian” strategy, the “corporate citizenship” strategy, and the “market failures” strategy. It constitutes an attempt to develop the market failures approach to reflect on CPAs. My main claim is that within such an account, the idea that corporations have a license to operate considerably limits their right to engage in political activities.